Strategic Approaches to Safeguarding the Digital Future: Insights into Next-Generation Cybersecurity - Chisty, Nur Mohammad Ali; Baddam, Parikshith Reddy; Amin, Ruhul (Engineering International, 2022)
This research investigates various strategic approaches to protecting the digital future and offers insights into the practices of the next generation of cybersecurity. The study's primary objectives are to identify key challenges and trends in the current cybersecurity landscape, evaluate the effectiveness of traditional cybersecurity approaches, investigate emerging technologies for enhancing cybersecurity resilience, examine human factors in cybersecurity resilience, and develop recommendations for future cyber defense. All of these objectives will be accomplished through the course of the study. To analyze strategic approaches to cybersecurity, the study uses a methodology based on a survey of secondary data and synthesizes the current literature from recognized sources. Among the most significant discoveries are the significance of incorporating new technologies, addressing human aspects, encouraging collaboration, and emphasizing risk management. Policy implications include promoting cooperation and the exchange of information, investing in emerging technologies, raising awareness about cybersecurity, building regulatory frameworks, and boosting international cooperation through the promotion of international cooperation. According to the findings of this study, organizations, policymakers, and other stakeholders looking to improve their cybersecurity resilience and effectively protect the digital future can benefit from the insightful insights and practical advice provided.
Keywords: Strategic Cybersecurity; Digital Future Protection; Next-Generation Defense; Safeguarding Strategies; Cyber Threat Intelligence; Future-proofing Security; Advanced Cyber Defense; Proactive Cybersecurity Measures; Digital Resilience Strategies; Cyber Threat Landscape